Regioselective Construction of Coumarin-1,2,4-triazines via a Cs2CO3-Catalyzed [3+3] Cycloaddition Reaction - Liu, Xuan-Yu; Zhang, Fa-Guang; Ma, Jun-An (Synlett, 2022)
A cesium carbonate (Cs2CO3)-catalyzed [3+3] cycloaddition reaction of coumarin-diazo reagents with glycine imino esters is established to produce tetrahydro-1,2,4-triazines in good yields with excellent regioselectivity. One-pot cycloaddition/oxidation protocol could further provide practical access to a series of new coumarin-decorated 1,2,4-triazines.
Keywords: triazine; cycloaddition; diazo reagent; coumarin; regioselectivity